1997
DOI: 10.1097/00006123-199711000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a High Free Radical State in Low-grade Astrocytomas

Abstract: We speculate regarding malignant transformation as a possible consequence of this decline in antioxidant capacity, as well as regarding the role of seizures and astrocytoma glutamate receptors in the initiation of free radical cascades. The therapeutic and teleological implications are considerable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…The present study showed that TBARS levels in the tested cancerous tissues are higher than those in normal tissues. These reports are coinciding with the earlier data (Louw et al, 1997;Rajeshwar et al, 2005). This emphasizes the reduction in free radical yield and the subsequent decrease in harm and damage to the cell membrane and decrease in MDA production.…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that TBARS levels in the tested cancerous tissues are higher than those in normal tissues. These reports are coinciding with the earlier data (Louw et al, 1997;Rajeshwar et al, 2005). This emphasizes the reduction in free radical yield and the subsequent decrease in harm and damage to the cell membrane and decrease in MDA production.…”
Section: Discussionsupporting
confidence: 92%
“…If left uncontrolled, these can harm cell membranes, energy metabolism, and DNA. To prevent such ROS damage, many cancer cells, including gliomas (Louw et al, 1997) show increased synthesis of glutathione (Jefferies et al, 2003) requiring enhanced cystine uptake (Wu et al, 2004). This explains the here-observed high levels of expression of both the catalytic and regulatory subunit of system x c Ϫ in glioma cells from biopsies and in glioma cell lines.…”
Section: System X Cmentioning
confidence: 68%
“…Therefore, the apoptotic effect of NO could be mediated, at least partially, by nitration of some key proteins triggering apoptosis [25,26]. Assuming that SIN-1 can simultaneously generate superoxide and nitric oxide which results in peroxynitrite formation [27], this compound appears as a useful tool to study the role played by protein nitration in peroxynitrite-induced apoptosis of monocytes, although other oxidative changes cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%